My personal journey in observing the dynamic Iskandar Malaysia and its forgotten sea gypsies economic development contradictions and cultural change - Jamilah Ariffin (iResolve, 2014)
The author intends to raise the awareness of the public on the fragile and vulnerable position of the Orang Selatar in the quest of survival within the context of a modern, fast-paced world.